2015
DOI: 10.1016/j.nbd.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Purkinje cell activity is the cause of dystonia in a shRNA-based mouse model of Rapid Onset Dystonia–Parkinsonism

Abstract: Loss-of-function mutations in the α3 isoform of the sodium pump are responsible for Rapid Onset Dystonia-Parkinsonism (RDP). A pharmacologic model of RDP replicates the most salient features of RDP, and implicates both the cerebellum and basal ganglia in the disorder; dystonia is associated with aberrant cerebellar output, and the parkinsonism-like features are attributable to the basal ganglia. The pharmacologic agent used to generate the model, ouabain, is selective for sodium pumps. However, close to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 68 publications
3
71
0
Order By: Relevance
“…It was recently shown that in both genetic and pharmacologic models of rapid-onset dystonia parkinsonism (RDP), abnormal bursting cerebellar output underlies dystonia [43, 47, 66]. Studies have shown that acute knockdown or pharmacologic inhibition of the α3 isoform of the sodium pump, the protein mutated in human RDP, converts the normally regular activity of Purkinje cells to burst firing [43, 66]. This erratic Purkinje cell activity in turn modifies the activity of DCN neurons, resulting in highly irregular cerebellar output.…”
Section: The Relationship Between Cerebellar Neuronal Dysfunction Andmentioning
confidence: 99%
See 2 more Smart Citations
“…It was recently shown that in both genetic and pharmacologic models of rapid-onset dystonia parkinsonism (RDP), abnormal bursting cerebellar output underlies dystonia [43, 47, 66]. Studies have shown that acute knockdown or pharmacologic inhibition of the α3 isoform of the sodium pump, the protein mutated in human RDP, converts the normally regular activity of Purkinje cells to burst firing [43, 66]. This erratic Purkinje cell activity in turn modifies the activity of DCN neurons, resulting in highly irregular cerebellar output.…”
Section: The Relationship Between Cerebellar Neuronal Dysfunction Andmentioning
confidence: 99%
“…Data from animal models also implicates olivocerebellar pathways, particularly Purkinje cells and cerebellar nuclear neurons, in the pathophysiology of dystonia [43, 66, 89]. For instance, morphologically/physiologically defective Purkinje cells or Purkinje cell loss has been described in tottering mice, DYT1 knock-in mice, waddles mice and dt rats [8992].…”
Section: Relationship Between Cerebellar Neuronal Dysfunction In Animmentioning
confidence: 99%
See 1 more Smart Citation
“…Another dystonic mouse model developed using conditional genetics to regionally limit cerebellar dysfunction revealed Purkinje cell abnormalities causing dystonia-like postures [10] while progressive loss of Purkinje cell neurons reduced dystonia severity [11]. Further studies using dystonic rodent models localised the mechanism of action to Purkinje cell sodium pump dysfunction, leading to aberrant high frequency firing [12,13]. There is also accumulating evidence of cerebellar involvement in CD in humans.…”
Section: Introductionmentioning
confidence: 99%
“…For HDAC1 staining, the sections were treated in 10 mM citric acid (pH 6) for 15 minutes at 95 °C for antigen retrieval prior to the primary antibody incubation. Immunoreactivity was visualized by secondary antibodies conjugated with either Alexa Fluor 594 (HDAC1, Invitrogen, A11012) 8 or Alexa Flour 488 (HDAC2, HA, GFP, Invitrogen, A11008) 42 . The sections were incubated at a 1:200 dilution at room temperature for 2 hours, counter-stained with 4′,6-diamidino-2-phenylindole (DAPI), and then mounted on superfrost plus slides in Vectashield mounting media (Vector Laboratories).…”
Section: Methods Summarymentioning
confidence: 99%